(untitled) (Journal of Economics and Management Research, 2022)
ملخص : يهدف البحث إلى اختبار تأثير دعم الادارة العليا على التجديد الاستراتيجي الاستماري ، وتم اختبار البحث في الميدان التعليمي، وتمثلت عينته البحث بالملاكات التدريسية في عدد من كليات جامعة تكريت ، وتم اعتماد استمارة استبيان كأداة رئيسية لجمع البيانات ، إذ بلغت الاستبانات المستردة والصالحة التحليل 289 استبانة ، وتوصل البحث إلى مجموعة من النتائج أهمها؛ وجود أثر ذو دلالة معنوية لدعم الادارة العليا في التجديد الاستراتيجي الاستثماري في الكليات المبحوث. تصنيفات JEL : M52;M1;L3 Abstract: The research aims to test the impact of Support for senior management on strategic strategic renewal, and the research was tested in the educational field, and the research sample was represented by the teaching staff in a number of faculties of Tikrit University, and a questionnaire was adopted as a main tool for data collection, as the recovered and valid questionnaires reached 289 questionnaires, The research reached a set of results, the most important of which are; There is a significant effect of the foundations of knowledge sharing in the exploratory strategic renewal in the colleges under study. JEL Classification Codes: M52;M1;L3